It's Just a Fingertip! Yet Controversy Exists: Standardizing a Treatment Pathway for Pediatric Fingertip Injuries - Hilton P. Gottschalk, MD; Niamh D. McMahon, MS; Karen Piper, BS; Karla Lawson, PhD; Andrea Bauer, MD; Sonia Chaudhry, MD; Julie Samora, MD; Krister Freese, MD; Christine A. Ho, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: Pediatric fingertip injuries are very common; however, treatment varies greatly depending on geographic location and surgeon. A paucity of data exists on how emergency department practitioners and hand surgeons should treat these injuries. We sought to develop consensus around treatment guidelines for these injuries. Methods: We conducted a Delphi survey of self-identified pediatric hand surgeons. Participants answered care delivery questions about 11 scenarios of fingertip injuries. These included minor (e.g., <50% subungual hematomas without fractures) to severe injuries (e.g., complete to near-complete partial tip amputations). Each question was answered on a 3-point Likert scale and included inquiry about antibiotic use, clinical consults, treatment methods, and need for hand surgeon follow-up. The second round of Delphi asked the participants to view round-one responses and reanswer questions that had moderate kappa values (kappa = 0.40–0.69) to attempt to reach consensus. Results: Thirty-four surgeons took the first round of Delphi survey. Questions in each scenario ranged from very high to very poor levels of agreement. All but one scenario contained at least one question with moderate agreement allowing for resurvey and consensus building. Thirty-three (97%) of the same surgeons completed the second round. In the 11 scenarios, there were 22 questions resurveyed. Of those 22 questions, 17 (77%) changed to higher levels of consensus with a kappa ≥0.70, allowing consensus of expert opinion to be reached on 45 treatments. Conclusions: The panel reached consensus on when to use intravenous (IV), oral (PO) or no antibiotics for various scenarios of pediatric fingertip injuries. Clarification was achieved on the standard treatment and follow-up practices for multiple clinical scenarios. Further work is required to achieve expert consensus for management of multiple clinical scenarios. Key Concepts: (1) Fingertip traumas are commonly seen in pediatric emergency rooms with treatments varying widely depending on the region of care. (2) Oral (PO) antibiotics are recommended for a tuft fracture with nailbed displacement, a Seymour fracture, or during partial amputation without loss of vascularity, whereas IV and PO antibiotics are indicated for complete and near-complete amputation. (3) Hand surgeon consultation was recommended for Seymour fracture, partial amputation of the distal phalanx, and complete or near-complete amputation with loss of vascularity. (4) Further research needs to be done to achieve consensus on treatment of some traumas. Level of Evidence: V, Expert Opinion